The Policy Implementation of Taxes on Micro and Macro Economy in Indonesia - Parhani, Fajrin Mubarokah; Juarsa, Eka; Garnasih, Titi Ratna; Mulyawan, Setia (Communication in Research and Publications (CRP), 2025)
The implementation of taxes in Indonesia is often considered detrimental by the public, especially for microeconomic actors. Although the management of the State Revenue and Expenditure Budget (APBN) is more focused on macroeconomics to maintain long-term economic sustainability, its impact on the microeconomy is still not optimal. Taxes in Islamic governance not only function as a fiscal instrument but also as a mechanism for wealth distribution and addressing social inequality. The Islamic taxation system supports economic sustainability and social welfare in the Muslim community, which is the majority in Indonesia. Ideally, the implementation of taxes in Indonesia should be able to adopt the principles of Sharia economics to achieve the welfare of society. This paper discusses the application of taxes on micro and macroeconomics in Indonesia, using qualitative research methods through literature review. Secondary data comes from literature such as journals and related scientific works.